PANDANGAN HAKIM TERHADAP DISPENSASI PERNIKAHAN ANAK DI BAWAH UMUR (Studi Kasus di Pengadilan Agama Kota Malang) - Anita Anita; Ahmad Subekti; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
Marriage is an important event in human life because marriage is not only related to the two candidates' personal husband, but also involves family and community affairs, for those who are married must meet certain conditions, one of them is age. If one prospective bride does not meet the specified age requirements, she must file a marriage dispensation at the local Religious Court. Therefore, the researcher conducts research on